Literasi Media Berbasis Kearifan Lokal di Tanjung Pura Kabupaten Langkat Sumatera Utara - Mazdalifah Mazdalifah; Yovita Sabarina Sitepu; Fatma Wardy Lubis (Universitas Medan Area, 2019)
Media literacy is the ability in terms of using, analyzing, selecting and creating messages properly. Consequently, it become very important since people easily found fake news (hoax) or hate speech in daily life. These type of news shaped negative effects to people's lives, for example: divide people to against each other. One of the efforts to prevent the negative’s effect of Hoax or Hate speech is by empowering public with media literacy so they can use, analyze, select and creating messages properly. Efforts to empower media literacy can utilize from local wisdom which preserved by the community. The Tanjung Pura Malay community has local wisdom in the form of polite and gentle speech habits, using ornate words called pantun. Local wisdom issued by the Malay people of Tanjung Pura can be a barrier when they receive bad messages from Hoax and Hate speech.